Customizing the degradation and load-bearing profile of 3D polycaprolactone-tricalcium phosphate scaffolds under enzymatic and hydrolytic conditions - Yeo, A (Wiley, 2024)
Journal of Biomedical Materials Research - Part B Applied Biomaterials